Ireland : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that in 2003, the economy of Ireland rebounded with GNP growing by almost 3 percent. Recent indicators suggest that activity has continued to strengthen in 2004. During 2003, inflation decelerated and is now close to the euro area average. Most recently, however, oil price increases have led to a mild pickup in inflation. IMF staff projects that the economic recovery will gain momentum with GNP growth of 4 1\2 percent in 2004, accelerating slightly to 5 percent in 2005. Core inflation is forecast to stay close to 2 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet